Optimization and Mechanism Elucidation of Catalytic Photodegradation Methylene Blue by TiO2/Zeolite Coal Fly Ash Nanocomposite Under H2O2 Presence - Kusumawardani, Linda Jati; Widdyanti, Tutik; Iryani, Ani; Hasanah, Uswatun; Nurlela, Nurlela (Sains Natural: Journal of Biology and Chemistry, 2024)
The synthetic dye methylene blue is utilized in many industries. However, it harms the aquatic ecosystem. Methylene blue causes wastewater to become colored. If this colored waste is released into the environment, clean, colorless water will become colored. This work uses a zeolite coal fly ash/TiO2 nanocomposite to enhance the process and identify the photodegradation mechanism of Methylene Blue (MB). Our group has successfully synthesized this nanocomposite using a developed method, improving the materials' capacity for both photodegradation and adsorption. This study has proved nanocomposite performance to degrade methylene blue as a synthetic dye by optimizing the effects of H2O2 addition, catalyst dosage, pH, initial concentration of methylene blue, and irradiation period. The maximum photodegradation in this investigation was observed at a pH of 12 with a nanocomposite dose of 3 g/l and an addition of 8 ml/l of H2O2, and in this study, degradation efficiency reached 100% for an 18 mg/l MB concentration in a short period of 75 minutes. With a reaction rate constant of 0.0601 min-1, the reaction kinetics were described by a pseudo-first-order reaction kinetics model. UPLC-MS/MS QToF analysis revealed the result of chemicals produced by photocatalytic degradation of methylene blue fragmentation into simpler molecules.